Competition Policy: Administrative-Territorial Aspect - Artem Vladimirovich Polenov (Управленческое консультирование, 2018)
In this article the analysis of validity and expediency of improvement of the mechanism of realization of a competition policy on more isolated territorial units, such as is offered: territorial subject of the Russian Federation, municipal territorial unit. Regional and municipal features of carrying out policy in the field of development and protection of the competition are investigated. Tasks of providing the competitive relations in territories of municipal territorial unit.